Conserved Metabolic Changes in Nondiabetic and Type 2 Diabetic Bariatric Surgery Patients: Global Metabolomic Pilot Study - Konrad Sarosiek; Kirk L. Pappan; Ankit V. Gandhi; Shivam Saxena; Christopher Y. Kang; Heather McMahon; Galina I. Chipitsyna; David S. Tichansky; Hwyda A. Arafat (Journal of Diabetes Research)
The goal of this study was to provide insight into the mechanism by which bariatric surgical procedures led to weight loss and improvement or resolution of diabetes. Global biochemical profiling was used to evaluate changes occurring in nondiabetic and type 2 diabetic (T2D) patients experiencing either less extreme sleeve gastrectomy or a full gastric bypass. We were able to identify changes in metabolism that were affected by standard preoperation liquid weight loss diet as well as by bariatric surgery itself. Preoperation weight-loss diet was associated with a strong lipid metabolism signature largely related to the consumption of adipose reserves for energy production. Glucose usage shift away from glycolytic pyruvate production toward pentose phosphate pathway, via glucose-6-phosphate, appeared to be shared across all patients regardless of T2D status or bariatric surgery procedure. Our results suggested that bariatric surgery might promote antioxidant defense and insulin sensitivity through both increased heme synthesis and HO activity or expression. Changes in histidine and its metabolites following surgery might be an indication of altered gut microbiome ecology or liver function. This initial study provided broad understanding of how metabolism changed globally in morbidly obese nondiabetic and T2D patients following weight-loss surgery.